Utilization of E-Commerce and Digital Marketing in Increasing Customer Purchasing Decisions at CV. CS Lestari Jaya Kisaran - Michael; Sri Rezeki (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
At CV. CS Lestari Jaya, a decline in sales is evident due to a continuous decrease in customer purchases. This drop in customer purchasing decisions may be linked to the company's limited use of e-commerce and digital marketing strategies. The aim of this study is to assess how the use of e-commerce and digital marketing can influence customer purchasing decisions at CV. CS Lestari Jaya Kisaran. This research is quantitative in nature, with a population of 149 customers who made purchases at CV. CS Lestari Jaya Kisaran in 2023. The sample size was determined using the Slovin formula with a 5% standard error, resulting in 109 samples. The findings indicate that both e-commerce and digital marketing have a significant impact on customer purchasing decisions, both individually and together. To enhance customer purchasing decisions, it is crucial for CV. CS Lestari Jaya Kisaran to effectively leverage e-commerce platforms and digital marketing strategies. Furthermore, running targeted paid advertising campaigns on these platforms can help reach specific audiences based on demographics and interests, increasing the likelihood of conversions